Reoperation rates after breast conserving surgery for breast cancer among women in England: retrospective study of hospital episode statistics. (12th July 2012) - Jeevan, R; Cromwell, D A; Trivella, M; Lawrence, G; Kearins, O; Pereira, J; Sheppard, C; Caddy, C M; van der Meulen, J H P
Abstract : Objectives To examine whether rate of reoperation after breast conserving surgery is associated with patients' characteristics and investigate whether reoperation rates vary among English NHS trusts. Design Cohort study using patient level data from hospital episode statistics. Setting English NHS trusts. Participants Adult women who had breast conserving surgery between 1 April 2005 and 31 March 2008. Main outcome measure Reoperation rates after primary breast conserving surgery within 3 months, adjusted using logistic regression for tumour type, age, comorbidity, and socioeconomic deprivation. Tumours were grouped by whether a carcinoma in situ component was coded at the time of the primary breast conserving surgery. Results 55 297 women had primary breast conserving surgery in 156 NHS trusts during the three year period. 11 032 (20.0%, 95% confidence interval 19.6% to 20.3%) women had at least one reoperation. 10 212 (18.5%, 18.2% to 18.8%) had one reoperation only; of these, 5943 (10.7%, 10.5% to 11.0%) had another breast conserving procedure and 4269 (7.7%, 7.5% to 7.9%) had a mastectomy. Of the 45 793 women with isolated invasive disease, 8229 (18.0%) had at least one reoperation. In comparison, 2803 (29.5%) of the 9504 women with carcinoma in situ had at least one reoperation (adjusted odds ratio 1.9, 95% confidence interval 1.8 to 2.0). Substantial differences were found in the adjusted reoperation rates among the NHS trusts (10th and 90th centiles 12.2% and 30.2%). Conclusion : One in five women who had breast conserving surgery in England had a reoperation. Reoperation was nearly twice as likely when the tumour had a carcinoma in situ component coded. Women should be informed of this reoperation risk when deciding on the type of surgical treatment of their breast cancer.